The association between socioeconomic position and depression or suicidal ideation in low- and middle-income countries in Southeast Asia: a systematic review and meta-analysis - Lucy Barrass; Elisha Joshi; Joshua Dawe; Bruna Rubbo; Maria Theresa Redaniel; Lucy Riglin; Nanette R. Lee; Laura D. Howe; Duleeka Knipe (BMC Public Health)
Abstract Background Mental illnesses contribute to a significant burden of disease in low- and middle- income countries (LMICs). Understanding risk factors for poor mental health is essential to reducing the burden, and for preventative measures to be implemented. The role of socioeconomic position (SEP) in poorer mental health is well established in high income countries, but less is known in LMICs. This study aimed to identify and synthesise epidemiological evidence for the associations between SEP and depression and suicidal ideation in LMICs in Southeast Asia, and to describe the strength and direction of any associations identified. Methods This systematic review identified evidence by searching four databases in February 2023 (Medline, Embase, PsycInfo and Web of Science), grey literature and reference searching of included papers. Papers were included if they were based in a Southeast Asian LMIC general or hospital populations (= 16 years of age) and explored at least one measure of SEP in association with depression or suicidal ideation. Study quality was assessed using the Joanna Briggs Institute tool. A meta-analysis and narrative synthesis were performed. Results Fifty-nine papers from six out of nine Southeast Asian LMICs were identified, with education the most commonly examined measure of SEP. Several papers explored more than one measure of SEP. Around half of the papers were rated as higher quality. Meta-analyses of education (OR: 1.87, 95% CI: 1.49-2.35) and working status (OR: 1.30, 95% CI: 0.99-1.71) provided evidence of lower levels of education and not being employed being associated with higher odds of depression. Consistent associations between lower SEP and higher odds of depression were also found for financial difficulty and subjective economic status. Three papers used suicidal ideation as their outcome, and there was some evidence of an association with lower SEP and higher ideation. Conclusions Evidence indicates that lower SEP is associated with higher likelihood of depression, whereas for suicidal ideation, the evidence available is insufficient to reach a conclusion. The lack of longitudinal studies prevents the temporal nature of these associations being established. Systematic review registration PROSPERO: CRD42023410444.